High-performance intrinsic low-k polymer via the synergistic effect of its three units: adamantyl, perfluorocyclobutylidene and benzocyclobutene. Issue 73 (19th July 2016) - Kong, Lingqiang; Qi, Tianke; Ren, Zhidong; Jin, Yunxia; Li, Yan; Cheng, Yuanrong; Xiao, Fei
Abstract : Intrinsic highly cross-linked low- k benzocyclobutene polymer functionalized with adamantyl and perfluorocyclobutylidene. Abstract : Perfluorocyclobutylidene (PFCB) polymers have gained much interest as the next generation fluoropolymers due to their low dielectric constant, low surface energy, thermal and thermal oxidative stability and chemical resistance. Herein, we obtained a low- k cross-linked polymer by incorporating the bulk rigid adamantyl, perfluorocyclobutylidene and benzocyclobutene groups into a single monomer. The k value of the obtained polymer was 2.38 and the dielectric loss was less than 0.0004 at 1 MHz due to the effect of the C–F bond and the bulk rigid adamantyl group. The polymer film also showed excellent uniformity and planarity with a surface roughness of less than 0.60 nm on a 1 × 1 μm 2 area and good hydrophobicity with a water contact angle of 113.5°. Due to the highly cross-linked network structure and the introduction of the rigid adamantly group, the polymer exhibited a high Young's modulus, high hardness and good thermal stability ( T d > 400 °C in nitrogen).